Improving Students' Listening Ability through Chain Message Games in Class II Indonesian Language Subjects at Madrasah Ibtidaiyah - Natalia, Nova; Zulaiha, Siti; Meldina, Tika (Universitas Islam Negeri Raden Intan Lampung, 2024)
The aim of the research is to determine the increase in students' listening skills through chain message games in Class II Indonesian Madrasah Ibtidaiyah subjects. The type of this research is Classroom Action Research using the Kurt Lewin model. The subjects of this research were class II MI students. Data collection techniques use participant observation, tests and documentation. Data analysis uses quantitative and qualitative analysis. The research results showed that in Cycle I the number of students who completed was 10 students with a percentage of 58.80%, while in Cycle II all students completed with a percentage of 100% and in the very good category. Increasing listening skills through chain message games in Indonesian language subjects in class II from pre-action, cycle I and cycle II experienced a significant increase where the average for pre-action was 68.8%, cycle I got 79.1% and cycle II namely 88.2%. It can be concluded that there is an increase in listening ability after using the chain message game technique in class II MI Indonesian language subjects.